FIGURES OF SPEECH IN WESTLIFE’S SELECTED SONGS - Marito Portune Tambun; Yunita Agnes Sianipar (LINGUISTICA, 2014)
ABSTRACT This study deals with the figures of speech used in the lyrics of Westlife’s Selected Songs. The objectives of the study are to describe the types of figures of speech used inWestlife’s Selected Songs, to derive the figures of speech usedin Westlife’s Selected Songs,and to reason why they are  found in Westlife’s Selected Songs . The research was conducted by descriptive qualitative design. The data was the lyrics ofWestlife’s Selected Songs, the data were collected from 10 songs that has figures of speech.  The data were analyzed by identifying and classifying the figures of speech displaying the result in a table. Then these figures of spech was described in details. It was found that there was eight types of figures of speech which used; they areSimile 27,71%, Metaphor 21,70 %, Personification 1,20 %,Synecdoche 1,20 %, Metonymy 7,23 % , Symbol 4, 81 %,  Hyperbole 33,75 % and Paradox 2,40 %.The most frequent type of figures of speech used in the lyrics of Westlife’s Selected Songs was Hyperbole.   Keyword :Literature , Figures of Speech,Song